Digital Business Model Utilization for Monetizing the Lofi for Today YouTube Channel through a Technopreneurship Approach - Faruk Muhamad (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The rapid growth of the digital creative industry has created new opportunities for content creators to generate revenue through various monetization models. However, Lofi for Today still relies primarily on YouTube AdSense, while studies integrating the Business Model Canvas (BMC), SWOT analysis, and a technopreneurship approach to develop sustainable business models for independent lofi music channels remain limited. This study aims to design an adaptive and sustainable digital business model to enhance the monetization of the Lofi for Today YouTube channel. A descriptive qualitative approach was employed, with data collected through literature reviews, channel observations, and interviews with creative industry practitioners. The data were analyzed using BMC and SWOT analysis as the basis for formulating business development strategies. The results indicate that revenue diversification through AdSense, channel memberships, donations, music licensing, merchandise, affiliate marketing, and brand collaborations can reduce dependence on a single revenue source. The technopreneurship approach also promotes the use of digital technologies and Artificial Intelligence (AI) to improve content production efficiency. Thus, the proposed model offers an innovative, adaptive, and sustainable business development strategy for digital content creators.